Parental counseling from the perspective of school pedagogists - Zuković Slađana N.; Slijepčević Senka D.; Turudić Jovana Z. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
This paper highlights the challenges of school pedagogists related to parental counseling. Counseling is a priority professional domain of school pedagogists' work and has a significant role in ensuring adequate conditions for quality socio-emotional and academic development of students. Therefore, this study examined practical experiences of school pedagogists in parental counseling. For research purposes, a semi-structured interview was used on a sample of 81 pedagogists in elementary schools in the Republic of Serbia (territory of AP Vojvodina). The obtained results were analyzed through qualitative thematic analysis. The research results show that the interviewed pedagogists regularly perform counseling with parents. However, they often face the parental resistance and reluctance to accept advice and fulfill established agreements. Primary reasons for engaging in parental counseling are difficulties in learning and lack of school progress, behavioral issues, and problems in family system. Besides, pedagogists recognize the necessity for further empowerment of competencies in counseling with parents, particularly emphasizing the importance of external support that helps them overcome stress and prevent professional burnout. It is concluded that empowering the counselor role of pedagogists in their work with parents requires professional, continuous and systemic support. This support is essential for creating optimal conditions that could facilitate the effective implementation of quality parental counseling practices.